A study of compliment response strategies among Malays and Iranians / Leila Afsari - Afsari, Leila (2012)
This study investigates and compares compliment response strategies (CRS) among Malays and Iranians with the aim of performing a semantic and pragmatic analysis of complimentary speech acts among Malays and Iranians. The data were collected through the use of interview and Discourse Completion Task (DCT), using eight complimentary sentences. Two were on appearance, two on character, two on ability and two on possession. A total of thirty university-students of the University of Malaya and University Putra Malaysia participated in the study over a period of three months. The findings demonstrated that all Malays and Iranians accepted most of compliments but Malays tended to reject more than Iranians. Although both groups accepted compliments, their strategies for acceptance were different from each other; Malays used more evade strategies than Iranians. Also Iranians used "taarof" strategy as a specific strategy related to Iranian culture for accepting a compliment. The most interesting thing was that "Thank you" was used for accepting compliments as the most frequent strategy among both groups.